Transcript profiling of salt tolerant tobacco mutants generated via mutation breeding - Ekşioğlu, Aybüke; Akdaş, Enes Yağız; ÇELİK, ÖZGE (Elsevier, 2018)
The main aim of the study is to identify the genes differentially, predominantly or specifically expressed in salt tolerant tobacco mutants, improved from Akhisar 97 and İzmir Özbaş varieties via mutation breeding, with respect to unstressed control plants. Seven tobacco mutants which have different salt tolerance capacities were evaluated by Gene Fishing analysis. Under stress conditions differentially expressed 100 reproducible bands were identified (74 of up-regulated and 20 of down-regulated while 6 were unknown). 75 of differentially expressed genes (DEGs) were successfully extracted from the gel and sequence analyses were performed. Functional annotation of the DEGs was performed against Blastn by interrogating their sequences. The 65 salt-regulated differentially expressed genes showed similarity with known genes, while 6 of DEGs didn't show any genetic similarities with known genes. DEGs were classified in eleven functional categories involving the abiotic stress response, biotic stress response, energy metabolism, cellular transport, catalitic activity, protein modification, amino acid metabolism and transcription factors. All the mutants were evaluated for their regulatory mechanisms against salt stress. The current data reveal that these six DEGs should be identified by next generation sequencing techniques and functional analysis should be design to understand the role of these six differentially expressed genes of tobacco mutants in further studies to improve new genetic resources.
Keywords: Differentially expressed gene; Salt tolerant mutant; Transcript analysis